Erratum to ‘Efficacy and safety of local fibrinolytic therapy in intracranial hemorrhages: A systematic review and meta-analysis of randomised controlled trials’ [World Neurosurgery: X (22C) (2024) 100316] - Arun Babu Rajeswaran; Arshad Ali; Saleh Safi; Ahmed Eid Abdulghani Saleh (World Neurosurgery: X, 2025)
Background: Local fibrinolytic therapy for ICH and IVH are used to dissolve clots, but their role remains debatable. This review aims to study the efficacy and safety of local fibrinolytic therapy. Methods: Medline, Embase, CINAHL Plus, Cochrane, Scopus, Web of science, clinical trials.gov, WHO and EU Clinical Trials Register were searched for RCTs only, on intra-clot fibrinolytics vs standard treatments for ICH and IVH. Results: Thirteen RCTs were included in the final data synthesis. In pooled analysis for IVH, fibrinolysis vs saline showed reduced mortality [RR-0.63 (0.46, 0.85)], less risk of ventriculitis [RR-0.59 (0.35, 1.00)] and higher daily reduction in clot size percentage [SMD-0.93 (0.39, 1.47)] with fibrinolysis but found no significant difference in functional outcome [RR-1.07 (0.88, 1.30)], in the risk of new bleedings [RR-1.36 (0.44, 4.23)] and shunt-dependent hydrocephalus (RR-1.10 [0.77, 1.59)]. In pooled analysis for ICH, with fibrinolysis vs standard craniotomy, there was a reduced mortality [RR-0.65 (0.20, 2.51)] with decreased risk for new hemorrhages in the fibrinolysis arm [RR-0.48 (0.30, 0.78)] while in fibrinolysis vs standard medical treatment, the trend was also a reduced mortality [RR-0.83 (0.65, 1.05)] with favourable outcome [RR-1.20 (1.00, 1.44)] and higher risk of new bleeds (RR-2.27 [1.23, 4.19]) but no significant difference in brain infections (RR-1.34 [0.24, 7.49]). Conclusion: Local fibrinolytic therapy in ICH and IVH decreases mortality and improves the clot resolution but shows no substantial gain in the good functional outcome and has increased risk of new hemorrhages. Further studies required to consolidate evidence for their efficacy and safety.